2020
DOI: 10.3390/nu12030792
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Gut Microbiota in Children with Autism Spectrum Disorder: A Systematic Review and Meta-Analysis

Abstract: Background: Autism spectrum disorder (ASD) is a public health problem and has a prevalence of 0.6%–1.7% in children. As well as psychiatric symptoms, dysbiosis and gastrointestinal comorbidities are also frequently reported. The gut–brain microbiota axis suggests that there is a form of communication between microbiota and the brain underlying some neurological disabilities. The aim of this study is to describe and compare the composition of gut microbiota in children with and without ASD. Methods: Electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
157
6
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(225 citation statements)
references
References 69 publications
8
157
6
4
Order By: Relevance
“…Rather, we propose that GI exposure to p-Cresol triggers ASD behaviors by inducing a selective microbiota dysbiosis, which is sufficient to fully induce social behavior deficits and partially stereotypies upon transplantation to control mice. We indeed show that a p-Cresol-rich environment reduces bacterial b-diversity, as described in ASD patients [6][7][8] , and provides a selective growth advantage for several taxa, in line with a previous in vitro study 26 . The correlation between the abundances of 26 OTU and social behavior argues for a clear link between certain bacterial taxa and social abilities.…”
Section: P-cresol-induced Dysbiosis Modulates the Social Behavior Ofsupporting
confidence: 90%
See 2 more Smart Citations
“…Rather, we propose that GI exposure to p-Cresol triggers ASD behaviors by inducing a selective microbiota dysbiosis, which is sufficient to fully induce social behavior deficits and partially stereotypies upon transplantation to control mice. We indeed show that a p-Cresol-rich environment reduces bacterial b-diversity, as described in ASD patients [6][7][8] , and provides a selective growth advantage for several taxa, in line with a previous in vitro study 26 . The correlation between the abundances of 26 OTU and social behavior argues for a clear link between certain bacterial taxa and social abilities.…”
Section: P-cresol-induced Dysbiosis Modulates the Social Behavior Ofsupporting
confidence: 90%
“…Children with ASD and concurrent GI symptoms exhibit more pronounced social impairments, sensory overresponsivity and anxiety compared to ASD peers without GI symptoms [3][4][5] . In addition, ASD patients exhibit gut microbiota dysbiosis characterized by reduced bacterial b-diversity and changes in the relative abundances of several bacterial taxa [6][7][8] . Dysbiosis in ASD patients is associated with altered urinary, plasmatic or fecal levels of microbial metabolites such as shortchain fatty acids (SCFA), indoles and tyrosine-derived metabolites [9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the genus level, controversial findings were more often reported [Ho et al, 2020], though a meta-analysis reported five genera (Bacteroides, Parabacteroides, Clostridium, Faecalibacterium, and Phascolarctobacterium) more abundant in ASD children and two genera (Coprococcus and Bifidobacterium) significantly decreased [Iglesias-Vazquez et al, 2020]. In our study, two butyrateproducing genera, Clostridium clusters IV and XIVa, were less prevalent in the gut microbiota of autistic children compared to in the control group.…”
Section: Discussioncontrasting
confidence: 57%
“…Indeed, the observed gut microbiota changes across ASD studies were often contradictory [Ho et al, 2020;Iglesias-Vazquez, Van Ginkel Riba, Arija, & Canals, 2020]. Bacterial phyla Bacteroidetes, Firmicutes, and Proteobacteria have been reported more abundant in ASD children [Iglesias-Vazquez et al, 2020], but some studies demonstrated an opposite result or no difference between children with ASD and healthy control [Ho et al, 2020].…”
Section: Discussionmentioning
confidence: 99%